Wet Gas Measurement - Henry, M; Tombs, MS (Canadian Intellectual Property Office, 2015)
A first apparent property of a multi-phase process fluid is determined based on the motion of the vibratable flowtube. One or more apparent intermediate values associated with the process fluid are determined based on the first apparent property. One or more corrected intermediate values are determined based on a mapping between the apparent intermediate values and the corrected intermediate values. One or more phase-specific properties of the multi-phase process fluid are determined based on the corrected intermediate values. A measure of wetness of the multi-phase process fluid is determined based on the one or more phase-specific properties that are determined based on the corrected intermediate values. A second apparent property of the multi-phase process fluid is determined using the differential pressure flowmeter. A phase-specific property of a phase of the multi-phase process fluid is determined based on the measure of wetness and the second apparent property.